2011
DOI: 10.1016/j.physleta.2011.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Stability of traveling pulses of cubic–quintic complex Ginzburg–Landau equation including intrapulse Raman scattering

Abstract: The complex cubic-quintic Ginzburg-Landau equation (CGLE) admits a special type of solutions called eruption solitons. Recently, the eruptions were shown to diminish or even disappear if a term of intrapulse Raman scattering (IRS) is added, in which case, self-similar traveling pulses exist. We perform a linear stability analysis of these pulses that shows that the unstable double eigenvalues of the erupting solutions split up under the effect of IRS and, following a different trajectory, they move on to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The erupting solitons have been found numerically [12] on a relatively large region of the CGLE parameter space, and were experimentally observed in passively mode-locked lasers [14]. Recently, the eruptions were shown to change or even cancel by the introduction of one or more additional terms in the CGLE [15][16][17][18][19][20]. In fact, in [18,19] we have shown that the intrapulse Raman scattering (IRS), if sufficiently strong, may move one or both unstable eigenvalues to the stable region, thus eliminating the eruptions on one side, or on both sides, of the pulse.…”
Section: Introductionmentioning
confidence: 99%
“…The erupting solitons have been found numerically [12] on a relatively large region of the CGLE parameter space, and were experimentally observed in passively mode-locked lasers [14]. Recently, the eruptions were shown to change or even cancel by the introduction of one or more additional terms in the CGLE [15][16][17][18][19][20]. In fact, in [18,19] we have shown that the intrapulse Raman scattering (IRS), if sufficiently strong, may move one or both unstable eigenvalues to the stable region, thus eliminating the eruptions on one side, or on both sides, of the pulse.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been recently shown that the inclusion in the CGLE of a term that, in optics, models the delayed Raman scattering, allows the existence of stable solutions in a parameter region where the background is also stable [4]. Note that this higher order term has also been associated with the stabilization of erupting solitons of the quintic CGLE [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between third-order dispersion and other higher-order effects become important for stable pulse generation [15,16]. The influence of different HOEs on the exploding LSs in the CQGLE was studied numerically in [16][17][18][19][20][21][22][23]. In particular, it was shown that a proper combination of the three HOEs can provide a shape stabilization of an exploding LS.…”
mentioning
confidence: 99%